Analisis Pelaksanaan Pengikatan Muatan Kontainer Di Kapal MV. Tanto Tenang Berdasarkan Standar Peralatan Lashing - Arief Supriatna (Jurnal Pendidikan Manajemen Transportasi, 2024)
Ships are chosen as the main means of sea transportation, because the delivery of goods can be carried out in large quantities, and the costs incurred are smaller than other means of sea transportation. A container ship is a ship specifically designed to transport containers. On container ships, it is inseparable from the problem of tying container cargo such as, how to carry out container cargo tying on the MV ship. Tanto Tenang, and what causes the implementation of container cargo tying not to be in accordance with procedures, which are often found on container ships, especially regarding cargo lashing tools. The method used by the researcher is a qualitative method. The research data were obtained from primary data and secondary data, while data collection was obtained from observations, interviews, descriptive and literature. In the study on the analysis of the implementation of container cargo tying on the MV ship. Tanto Tenang based on lashing equipment standards, in the implementation it has not been in accordance with the Standard Operational Procedure, because in the implementation it is hampered by tools that are less supportive, the lack of lashing equipment for loading containers is one of the main causes. Because in its implementation, lashing tools are often lost and lacking. In container lashing, the lashing gang factor that does not understand the Standard Operational Procedure, cargo lashing is also another cause of the imperfect implementation of lashing on the ship. From the results of the study it can be concluded that the main cause of the cargo lashing process is due to lack of training for the lashing gang and the ship's crew themselves as well as the lack and loss of container cargo lashing equipment.